ヒガシオングル トウ ヨリ エタ ケイソウ ヨホウ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 福島, 博; フクシマ, ヒロシ; 綿貫, 知彦; ワタヌキ, トモヒコ; 小林, 艶子; コバヤシ, ツヤコ; FUKUSHIMA, Hiroshi; WATANUKI, Tomohiko; KO-BAYASHI, Tsuyako (国立極地研究所, 1973)
P(論文) In this paper are reported 18 taxa of diatom. Among these taxa, Achnanthes brevipes var. intermedia, Cyclotella stelligera, Cymbella tumida, Diatoma hiemale var. mesodon, Frustulia rhomboides, Gomphonema acuminatum var. coronata, Navicula muticopsis f. murrayi, Nav. radiosa var. tenella, Pinnularia gibba, P. g. var. parva, Stauroneis anceps, Synedra acus and S. ulna var. oxyrhynchus are newly recorded from East Ongul Island. departmental bulletin paper